2005
DOI: 10.1016/s0002-9440(10)62233-x
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of Telomere-Binding Proteins, TRF1, TRF2, and TIN2 Is Related to Telomere Shortening during Human Multistep Hepatocarcinogenesis

Abstract: The telomeric repeat-binding factor 1 (TRF1), TRF2, and the TRF1-interacting nuclear protein 2 (TIN2) are involved in telomere maintenance. We describe the regulation of expression of these genes along with their relationship to telomere length in hepatocarcinogenesis. The transcriptional expression of these genes, TRF1 protein, and telomere length was examined in 9 normal livers, 14 chronic hepatitis, 24 liver cirrhosis, 5 large regenerative nodules, 14 low-grade dysplastic nodules (DNs), 7 high-grade DNs, 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
90
2
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 136 publications
(102 citation statements)
references
References 37 publications
7
90
2
1
Order By: Relevance
“…17,18 Previous studies on dysplastic nodules and dysplastic foci of the liver demonstrated that telomere shortening occurs in the early stages of AB/f, anaphase bridge per high-power field; F/U, follow-up (months); M/f, mitosis per high-power field; MM/f, multipolar mitosis per high-power field; NA, data not available; TA(T), telomerase activity (tumor), TL ratio, telomere length ratio; TRF(T), telomere repeat frequency (tumor). hepatocarcinogenesis, 10,11,19 again providing evidence for the importance of telomere dysfunction in cancer initiation. However, not all preneoplastic lesions are considered to be capable of fully advancing to cancer.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…17,18 Previous studies on dysplastic nodules and dysplastic foci of the liver demonstrated that telomere shortening occurs in the early stages of AB/f, anaphase bridge per high-power field; F/U, follow-up (months); M/f, mitosis per high-power field; MM/f, multipolar mitosis per high-power field; NA, data not available; TA(T), telomerase activity (tumor), TL ratio, telomere length ratio; TRF(T), telomere repeat frequency (tumor). hepatocarcinogenesis, 10,11,19 again providing evidence for the importance of telomere dysfunction in cancer initiation. However, not all preneoplastic lesions are considered to be capable of fully advancing to cancer.…”
Section: Discussionmentioning
confidence: 97%
“…8,9 Hepatocellular carcinoma (HCC) is the seventh most common cancer worldwide, accounting for the highest number of adult malignancies in areas endemic for hepatitis B virus (HBV). Telomere shortening is an early event in multistep hepatocarcinogenesis, occurring in preneoplastic lesions of dysplastic nodules 10,11 and shortened telomeres have been reported to induce chromosomal instability in hepatocytes, especially important in HBV-related hepatocarcinogenesis. 12,13 However, the roles of telomere dysfunction and telomerase parameters in the progression of human HCCs have not been systematically analyzed.…”
mentioning
confidence: 99%
“…8 Similarly, TRF2 has been found overexpressed in other types of human cancer, such as breast tumors, liver hepatocarcinomas and lung carcinomas. 19,20 Interestingly, overexpression of TRF2 in the case of human heptocarcinomas correlated with progressive telomere shortening, further demonstrating an important role of TRF2 in telomere length. 20 …”
Section: Short Telomeres Produced By Trf2 Overexpression Promote Tumomentioning
confidence: 89%
“…7,8 In this study, telomere length showed a gradual shortening during hepatitis B virus-related multistep hepatocarcinogenesis, which was consistent with earlier reports. 12,13 The micronucleus, an indicator of chromosomal instability, was reported to be associated with an increase in chromosomal alteration in an in vitro and in vivo study. [14][15][16][17][18] The studies revealed that the frequency of micronuclei gradually increased during human multistep hepatocarcinogenesis.…”
Section: -30mentioning
confidence: 99%